MODERASI BERAGAMA VERSI KEMENTERIAN AGAMA: KAJIAN PADA UNIVERSITAS ISLAM DI MALANG - Benny Afwadzi; Miski; Wahyu Indah Mala Rohmana (Penamas, 2023)
This study investigated four moderate indicators coined by the Ministry of Religious Affairs (M0RA) among Muslim students. This study is essential because the MoRA has claimed moderation in its institution, but it has been questioned whether Muslim students studying at Islamic universities have implemented the practice. This article is the result of research with a qualitative approach conducted by conducting interviews with 36 students studying at three Islamic universities in Malang using purposive sampling. It has two focuses: 1) students' religious understanding and practice related to the four moderate indicators of the MoRA; and 2) the cause of the articulation of moderation, which leads to the implication of how to build moderate thoughts in students. The result of the study shows that there are differences in religious understanding and practice regarding the four moderate indicators of the MoRA. Indicators that have problems are tolerance and anti-violence in the intra-religious area, especially among minority sects. Meanwhile, two other indicators, namely national commitment and accommodativeness to local culture, appear to be in a safe area. The study also finds that "problematic" students were from social-humanities and religious study programs. Second, there are many reasons for the emergence of moderation among students, ranging from family background to the organization they are involved in. Thus, the authors present internalization and normalization as means of building moderate thoughts and attitudes in students.